Protection of Customer Personal Data in the Standard Clauses of the Privacy Policy of the Seabank Digital Bank Application - Nimas Yuski Nur Lailli; Josef Purwadi; Yokhebed Arumdika (Journal of Law Perspectives Review, 2026)
This study aims to analyze the validity of standard clauses in the privacy policy of PT Bank SeaBank Indonesia, particularly in relation to customer personal data protection, and to examine the legal consequences arising from such clauses under Indonesian law. The research employs a normative legal method with statutory and conceptual approaches, relying on primary, secondary, and tertiary legal materials analyzed qualitatively through prescriptive reasoning. The findings reveal that the standard clauses used in SeaBank’s privacy policy tend to position customers in a weaker bargaining position through a “take it or leave it” mechanism, granting broad authority to the bank in processing personal data. These clauses are often general, lack transparency, and do not fully comply with the principles of legality, transparency, and informed consent as required by the Personal Data Protection Law and Consumer Protection Law. Furthermore, certain clauses potentially limit the liability of the bank, which may contradict existing legal provisions. Consequently, such clauses may be declared null and void if proven detrimental to customers, and the bank may bear legal responsibility for resulting damages. In conclusion, stronger regulatory supervision, improved transparency, and enhanced legal and digital literacy are essential to ensure effective personal data protection in digital banking services.